Evaluation of Environmental Enrichment on Feed Intake and Growth Performance of Weanling Pigs - Jenna J. Bromm; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 360 pigs (DNA 200 × 400; initially 13.8 ± 1.83 lb BW) were used in a 42-d nursery trial to determine the effects of the addition of an environmental enrichment, in the form of ropes tied to the feeder dividers, on feed intake and growth performance of weanling pigs. Pigs were weaned at approximately 21-d of age and randomly assigned to 1 of 2 treatments with 5 pigs per pen and 36 pens per treatment. At placement, a rope was secured to each of the dividers in the feed pans of the feeder (3 ropes/feeder) and remained tied to the feeders from d 0 to 10. There was no statistical difference (P>0.10) in ADG, ADFI, or F/G in phases 1 or 2 for pigs in pens with or without ropes tied to the dividers in the feed pan. Feed intake was not recorded for phase 3, but there was no evidence of a difference in phase 3 ADG or final BW between treatments (P>0.10). There was no observed difference in daily feed disappearance from d 0 to 14 based on the presence or absence of the environmental enrichment used in this trial. These results indicate that exposing newly weaned pigs to an environmental enrichment, in the form of ropes tied in the divider of the feed pan, at placement into the nursery did not impact growth performance or feed intake.
Keywords: environmental enrichment; growth performance; nursery pigs; sensory attractant